Doing better for families - (:unkn) unknown (OECD Publishing, 2011)
All OECD governments want to give parents more choice in their work and family decisions. This book looks at the different ways in which governments support families. It seeks to provide answers to questions like: Is spending on family benefits going up, and how does it vary by the age of the child? Has the crisis affected public support for families? What is the best way of helping adults to have the number of children they desire? What are the effects of parental leave programmes on female labour supply and on child well-being? Are childcare costs a barrier to parental employment and can flexible workplace options help? What is the best time for mothers to go back to work after childbirth? And what are the best policies to reduce poverty among sole parents?
Keywords: Families; Families -- Parents and Parenting; Children; Child Care; Families and relationships; Child Care; Children; Families; Parents and Parenting; Families and relationships